Optimasi Sisa Bahan Baku Pada Industri Mebel Menggunakan Algoritma Genetika - Andika Indra Kusuma; Agus Wahyu Widodo; Mochammad Ali Fauzi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The problem of the utilization of raw materials in the furniture industry is the difficulty of cutting raw materials with the right combination of sizes. To adjust the furniture production requirements, standard-sized raw materials must be cut to fit the needs of the furniture model to be produced. If not done the exact calculation when cutting the raw materials will certainly produce a lot of waste materials unused. The abundance of unused raw materials is what causes the maximum profit can not be achieved so that optimization of the remaining raw materials needs to be done. In this research optimization of the remaining raw materials is done with Genetic AlgorithmCorner Junction (GA+CJ). Stages performed are initial population generation, mutation with Rectangle &Junction Gene Swap Mutation(RJGSM) and Rectangle Rotation Mutation(RRM), evaluation, and selection. The results obtained in the form of chromosome-shaped solution arrangement of pieces of material. The highest fitness is 0.0026 which means consuming 16 pieces of raw material located on generation input parameter as much as 120 generations, mutation rate equal to 0.9, and 60 populations.